Comparison of the effect of two training methods (webinar and group discussion) on improving the attitude and performance of health workers in providing counseling with fertility promotion approach - Raziyeh Rahmati; Talat Khadivzadeh; Habibollah Esmaily (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Due to the significant decrease in fertility in recent decades and the important role of health workers and health-care providers in providing healthy reproductive counseling, their training is necessary using effective educational methods. Webinar and group discussion (GD) are effective in this regard. This study was conducted to determine the most effective method and with the aim of comparing the effect of two training methods (webinar and GD) on the attitude and performance of health workers in providing counseling with fertility promotion approach in comprehensive health centers in Mashhad. METHODS: In this randomized trial study with a control group, 108 health workers working in health centers no. 2-3 and 5 of Mashhad entered the study and were randomly divided into three groups of training by webinar, GD, and control. Intervention groups received healthy fertility counseling skills in three training sessions. Research tools were demographic information questionnaires, fertility attitudes, and performance measurement checklists for fertility counseling. The questionnaires were completed in three groups at the beginning and after the completion of the interventions. Data analysis was performed by Chi-square test and one-way analysis of variance using SPSS software version 16. RESULTS: The analysis of variance test showed that before the intervention, there was no statistically significant difference between the three groups in terms of average scores of fertility attitude and performance scores of fertility counseling. After the interventions, the difference between the fertility attitude scores (P < 0.001) and the performance scores of fertility counseling (P < 0.001) was significant in the three groups. There was no significant relationship between demographic characteristics and attitude and performance. CONCLUSION: Teaching by webinar and GD promotes the attitude and performance of health workers in providing counseling with a fertility promotion approach. Therefore, it is recommended to use new educational methods such as webinar and GD to promote childbearing counseling, which has been emphasized in the country's population policies. Since the mean score difference for the webinar training method was the highest due to the mean scores, this method could be more effective than the GD method.